Optimalisasi Komunikasi Berbasis Komunitas untuk Meningkatkan Partisipasi Persit Kopassus dalam Program Bank Sampah - Rizqi Akmaliah; Esfandani Peni Indreswari (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Community-based waste management in military housing areas, particularly within the environment of Markas Komando Pasukan Khusus (Makopassus), still faces several challenges. This service initiative aims to enhance the participation of the Army Wives Association (Persit) members of Kopassus in the Waste Bank program through the optimization of communication strategies. The method employed is Participatory Action Research (PAR), which actively involves the community in all stages of the activity, from problem identification to evaluation. Activities were carried out through outreach, technical training, online and offline communication campaigns, and participatory evaluations. The results show significant changes, including the formation of a Waste Bank working group, improved household waste sorting behavior, the emergence of local leaders from among Persit members, and the growth of collective awareness toward circular economy-based waste management. These findings confirm that communication strategies tailored to the audience's characteristics and based on community-centered approaches can effectively drive social change within military environments. This program holds the potential for replication in similar communities to support sustainable development through community empowerment.